HIV Infection in the Elderly: Arising Challenges - Mpondo, Bonaventura C. T. (Journal of Aging Research, 2016)
Globally there is an increase in the number of people living with HIV at an advanced age (50 years and above). This is mainly due to prolonged survival following the use of highly active antiretroviral therapy. Living with HIV at an advanced age has been shown to be associated with a number of challenges, both clinical and immunological. This minireview aims at discussing the challenges encountered by elderly HIV-infected patients.